IMPROVING STUDENTS’ WRITING SKILL THROUGH INTERACTIVE BLOG AT IKIP MATARAM - Suhaili, Muhamad; Suadiyatno, Taufik (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2016)
This research is aimed to improve students? writing skill through Interactive Blog at English Department of IKIP Mataram. The subjects of the research were A class students of the fifth semester of English Department that consist of 45 students. This research was a Classroom Action Research that involved critical analyses of the situation in classroom and system in which they worked. These situations were structured institutionally with some cycles that consist of planning, acting, observing, and reflecting which can help to define issues and ideas. There were four techniques of data collection that  were applied in this research; they were observation, interview, questioner and objective test. The techniques of analyzing data in this research used analytical scoring rubric adapted from Weigle. There were five components presented in the analytical scoring rubric for writing, i.e., content, organization, vocabulary, language use, and mechanics. The result of this research showed that interactive blog could improve students? writing skill, It can be proved by some facts; first, related to the srudents? result, there was 82% who passed the passing grade (60). Second, the observation result of students? participation showed the good improvement from the first meeting until the last meeting. The last, the result of interview towards students and lecturer showed the positive response when the interactive blog was applied in improving students? writing skill. It created a situation of feeling free and enjoyable. The students can explore and share their idea or opinion with other friends. Therefore students can help each other to do whatever was necessary to succeed. These situation made students? writing skill and productivity were more increasing. In addition by using this media, students were able to improve their ability in working individually, students were able to build their own knowledge, students were able to find out steps in solving problem in writing. Based on the result of this research, it can be concluded that interactive blog is able to improve students writing skill at IKIP Mataram.